1991
DOI: 10.1016/0735-1097(91)90632-j
|View full text |Cite
|
Sign up to set email alerts
|

Coronary hemodynamics and myocardial metabolism in patients with syndrome X: Response to pacing stress

Abstract: Coronary hemodynamics, myocardial metabolism and left ventricular function at rest and after incremental atrial pacing were evaluated in 12 patients with stress-induced angina and ST segment depression, angiographically normal coronary arteries and no evidence of spasm, generally labeled as syndrome X, and in 10 normal subjects. At baseline study, great cardiac vein flow was comparable in patients and control subjects. During pacing, an equivalent rate-pressure product was reached in the two groups, but the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(67 citation statements)
references
References 19 publications
7
57
0
3
Order By: Relevance
“…The increment of flow during pacing was similar in the patients and the controls. The coronary flow response is analogous to the findings in several studies of patients with syndrome X (9,30). A microvascular dysfunction may be responsible for cardiac chest pain in some patients with syndrome X (30, 31).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The increment of flow during pacing was similar in the patients and the controls. The coronary flow response is analogous to the findings in several studies of patients with syndrome X (9,30). A microvascular dysfunction may be responsible for cardiac chest pain in some patients with syndrome X (30, 31).…”
Section: Discussionsupporting
confidence: 66%
“…Myocardial glucose extraction in patients with syndrome X is efficient at rest, but myocardial insulin resistance may explain the impaired ability to increase carbohydrate oxidation during pace stress (9).…”
Section: Introductionmentioning
confidence: 99%
“…When the rate pressure product is increased by incremental atrial pacing (Fig. 3), the fractional extraction of b-hydroxybutyrate remains high at ;40%, thereby continuing to support external cardiac work (37).…”
Section: Rationalementioning
confidence: 99%
“…Although lactate production is a candidate for indicator of myocardial ischemia, no conclusive results have been obtained in several previous reports. [5][6][7][23][24][25] PET is a non-invasive tool for evaluating myocardial metabolism, as well as myocardial perfusion, in vivo. 19,20 In the present study, focal or diffuse fasting FDG uptake, which strongly suggested anaerobic metabolism, was observed in all 24 patients and to our knowledge, this is the first clinical report demonstrating that the fasting FDG uptake by the myocardium is significantly increased in syndrome X.…”
Section: Myocardial Metabolism In Syndrome Xmentioning
confidence: 99%
“…[1][2][3][4] Myocardial ischemia in syndrome X was originally defined as exerciseinduced ischemic changes on the electrocardiogram (ECG), but recently, much attention has been focused on the dysfunction of the coronary microcirculation, such as impaired coronary flow reserve, [5][6][7][8][9][10][11] as the cause of myocardial ischemia. These considerations raise the possibility that structural alterations may be found histologically in small vessels of the myocardium; however, only a few studies have been reported and the results have not been consistent.…”
mentioning
confidence: 99%